2019
DOI: 10.3390/ani9110923
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Invasive Monk Parakeets (Myiopsitta monachus) and Other Bird Species during Nesting Seasons in Santiago, Chile

Abstract: Simple SummaryThe monk parakeet (Myiopsitta monachus) is an invasive species, unique in the parrot family for its ability to build large nest structures. This species became globally distributed, promoted in part due to the pet trade market, and now is considered a pest because of the economic losses they produce. During the reproductive seasons of 2017 and 2018, we registered interactions between invasive monk parakeets and resident bird species in Santiago, Chile. We observed positive and negative interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 50 publications
0
34
0
5
Order By: Relevance
“…Moreover, we monitored the community of medium-sized raptor species present in the study area, including the black kite Milvus migrans, the booted eagle Hieraaetus pennatus, the common buzzard Buteo buteo, the northern goshawk Accipiter gentilis, the red kite Milvus milvus and the peregrine falcon Falco peregrinus. Predation of monk parakeets by raptors has been recorded in its invaded range [20,24,27,84], as well in our study area, such as peregrine falcon [91] and golden eagle Aquila chrysaetos (E. Navarro pers. comm.).…”
Section: Study Area and Fieldworkmentioning
confidence: 67%
“…Moreover, we monitored the community of medium-sized raptor species present in the study area, including the black kite Milvus migrans, the booted eagle Hieraaetus pennatus, the common buzzard Buteo buteo, the northern goshawk Accipiter gentilis, the red kite Milvus milvus and the peregrine falcon Falco peregrinus. Predation of monk parakeets by raptors has been recorded in its invaded range [20,24,27,84], as well in our study area, such as peregrine falcon [91] and golden eagle Aquila chrysaetos (E. Navarro pers. comm.).…”
Section: Study Area and Fieldworkmentioning
confidence: 67%
“…Monk Parakeets were introduced in Santiago of Chile in the early 1970s, when parakeets were released in the northeast area of Santiago, from where they started to spread to the rest of the territory [ 20 ]. Nowadays, Monk Parakeets are considered to be one of the most harmful species of invasive birds in Chile due to their negative impact associated with agricultural, fruit, and ornamental trees [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…in fecal samples from Monk Parakeets captured in Northeast Santiago, Chile, was reported [ 5 ]. A second report described interactions between Monk Parakeets and other bird species in Santiago, Chile, revealing that parakeets and other species of birds can coexist pacifically [ 20 ]. Interestingly, this study showed that, as observed in other countries [ 21 ], other bird species make use of Monk Parakeet nests for breeding, evidencing Monk Parakeet’s role as an ecosystem engineer [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further environmental risks occur if captive birds escape. In addition to possible transmission of disease to other animals, the escaped birds sometimes establish breeding populations that have negative effects on some native species [ 23 ]. Examples of this include Rose-Ringed Parakeets ( Psittacula krameria) and Monk Parakeets ( Myiopsitta monachus) in European countries, where they are considered to be a major cause of biodiversity loss [ 24 ].…”
Section: Ethical Issues Associated With Keeping Pet Birdsmentioning
confidence: 99%